Clinical profile of visual disturbances in alcohol abuse: A cross-sectional observational study in a forensic medicine unit. - Kiran, A. Kranti; Shireesha, Dr. Anumula (Student's Journal of Health Research Africa, 2025)
Background: Alcohol abuse is a major public health issue with significant neuro-ophthalmic implications. Visual disturbances are often underrecognized in chronic alcohol users, yet they may serve as important clinical markers of toxicity and chronic damage. This study aimed to evaluate the clinical spectrum and ocular findings associated with alcohol abuse in patients presenting to a forensic medicine unit. Methods: This observational study included 100 individuals with a history of alcohol abuse presenting with visual complaints. Demographic details, duration and pattern of alcohol use, presenting visual symptoms, and ocular examination findings were systematically documented. Descriptive statistics were applied to analyze the data, and results were expressed as frequencies and percentages. Results: The mean age of participants was 37.8 ± 9.4 years, with most cases in the 30–39 year group. Males predominated (82%). Chronic heavy alcohol use was reported in 64% of cases, with a mean duration of 8.1 ± 3.1 years. The most frequent symptoms were blurred vision (42%), diplopia (18%), photophobia (15%), and transient visual obscurations (12%). Less common complaints included reduced visual acuity (10%), color vision defects (2%), and visual hallucinations (1%). Ocular findings included conjunctival congestion (28%), nystagmus (16%), sluggish pupillary reflexes (14%), optic disc pallor (12%), hyperemia (8%), and retinal hemorrhages (5%). Seventeen percent of participants had normal ocular examinations despite subjective complaints. Conclusion: Visual disturbances are common among individuals with alcohol abuse. Both reversible and irreversible ocular changes were observed, highlighting the importance of early ophthalmic evaluation in this population. Recommendations: Routine ophthalmic screening should be integrated into de-addiction and rehabilitation programs. Multidisciplinary collaboration between ophthalmologists, psychiatrists, and forensic specialists is essential to prevent long-term visual morbidity.